2015
DOI: 10.36876/acst.1005
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Analysis of the Musa Paradisiaca Peel, Using UHPLC-ESI, FTIR and Confocal Microscopy Techniques

Abstract: This paper addresses the use of enzymatic reactions and analytical techniques such as UHPLC-ESI, FT-IR, NMR and microscopy analysis to study the banana peel and generated compounds that could be valued as raw materials for food industrial applications. Materials and MethodsMethanol, Acetonitrile and Water HPLC grade were purchased from Sigma-Aldrich (St Louis, MO, USA). Common inorganic reagents and solvents used in the study were analytical grade. Silica

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Lu et al (2011) specified the wavenumber between 950 and 1,200 cm -1 as the main functional group of carbohydrates, whereas Khamsucharit et al (2018) found that the pectin of BP was the "fingerprint" region between 800 to 1,300 cm -1 . The FTIR absorption peak of six BPE indicates the existence of functional groups, like hydroxyl and carboxyl, in agreement with BPE of other studies (Memon et al 2009;Alejandra et al 2015;El-nafaty et al 2013;Thomas and Johney 2017).…”
Section: Antimicrobial Activitysupporting
confidence: 89%
“…Lu et al (2011) specified the wavenumber between 950 and 1,200 cm -1 as the main functional group of carbohydrates, whereas Khamsucharit et al (2018) found that the pectin of BP was the "fingerprint" region between 800 to 1,300 cm -1 . The FTIR absorption peak of six BPE indicates the existence of functional groups, like hydroxyl and carboxyl, in agreement with BPE of other studies (Memon et al 2009;Alejandra et al 2015;El-nafaty et al 2013;Thomas and Johney 2017).…”
Section: Antimicrobial Activitysupporting
confidence: 89%
“…Moreover, there is a medium-strong broader peak around a wavelength of 3600 cm -1 due to the presence of -OH hydrogen bond stretching vibration. According to the study of Miriam et al [37], this broadband is due to the presence of -OH in cellulose. Finally, the presence of a peak at 3745 cm -1 and 3845 cm -1 can be assigned to -N-H stretching.…”
Section: Ftir Analysis Results Of Banana Stem Coagulantmentioning
confidence: 97%
“…Lipid, fatty acid, protein, alkaloids, lignin and carboxylate ions were assigned at 2928.50 and 1389.95 cm −1 (de la Mata et al, 2012). The wavelength at 1583.77 cm −1 was assigned to the lignin polymer (Alejandra González Corona et al, 2015). The absorption band at 1030.33 cm −1 was assigned to C‐O stretching, C‐C stretching and C‐N stretching of phenol and polysaccharide (Kumar et al, 2012), whereas the peak between 817 and 922 cm −1 corresponded to the amine groups (Memon et al, 2009).…”
Section: Resultsmentioning
confidence: 99%